2023
DOI: 10.1007/s11356-023-29202-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitrates in Turkish waters: sources, mechanisms, impacts, and mitigation

Sabit Erşahin,
Bayram C. Bilgili

Abstract: Intensive technological developments, rapid population growth, unplanned urbanization, and excessive use of nitrogen fertilizers have caused water resources to be contaminated substantially by nitrates in Turkey as well as across the world as evidenced by the accumulated scienti c information. The information should be evaluated to draw a nationwide attention to the problem. The aim of this review article was to highlight the importance of nitrate (NO 3 ) contamination and to discuss the measures to be taken t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 103 publications
(123 reference statements)
0
0
0
Order By: Relevance
“…Maximum groundwater nitrate concentrations were consistently measured in between Tarsus and Karaduvar regions in 2020 (Table 3). Intensive irrigation in agriculture, rapid urbanization and the terrestrial inputs from the domestic wastewater and industrial discharges have led to nitrate pollution in surface waters and groundwater in Mersin Province (Özbay et al, 2012;Akçay et al, 2022;Akçay, 2023;Akçay et al, 2023;Erşahin & Bilgili, 2023;Türkeri et al, 2023). Study findings indicated that highest concentrations were consistently measured in the regions where human-induced pressures are very intense (Güler et al, 2012;Erşahin & Bilgili, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Maximum groundwater nitrate concentrations were consistently measured in between Tarsus and Karaduvar regions in 2020 (Table 3). Intensive irrigation in agriculture, rapid urbanization and the terrestrial inputs from the domestic wastewater and industrial discharges have led to nitrate pollution in surface waters and groundwater in Mersin Province (Özbay et al, 2012;Akçay et al, 2022;Akçay, 2023;Akçay et al, 2023;Erşahin & Bilgili, 2023;Türkeri et al, 2023). Study findings indicated that highest concentrations were consistently measured in the regions where human-induced pressures are very intense (Güler et al, 2012;Erşahin & Bilgili, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Study findings indicated that the highest groundwater nitrate concentrations were consistently measured in these regions due to the anthropogenic pressures caused to nitrate contamination that would lead to potential health hazards for the people that use groundwater of these nitrate contaminated regions (Table 1, Figure 2). Anthropogenic perturbations such as the increase in population and hence domestic sewage, and the excess use of chemical fertilizer in the agriculture highly enhances nitrate pollution in the groundwater that can cause to health risks for people who use groundwater for consumption (Güler et al, 2012;Li et al, 2012;Wu et al, 2012;Wu & Sun, 2016;Adimalla, 2020;Erşahin & Bilgili, 2023). Previous studies performed in the groundwater in Mersin Province showed an apparent nitrate pollution due to intensive irrigation in agriculture and industrial activities as well as rapid urbanization in Mersin Province have led to nitrate pollution in groundwater in Mersin Province (Erşahin & Bilgili, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations